Spatio-temporal analysis of rice production and trade between Southwest China and major rice producers in Southeast Asia - Geng, Yucong; Raza, Qurat-Ul-Ain; Bashir, Muhammad Amjad; Xie, Shufu; Song, Xuemei; Yan, Mingyue; Jia, Guodong; Liu, Ruotong; Ran, Wangfang; Long, Yupei; Zhou, Mengyuan; Rehim, Abdur; et al. (Frontiers in Plant Science, 2025)
Analyzing the spatial and temporal patterns in rice production and trade in the southwestern region of China and the main rice-producing countries of Southeast Asia provides a reference for trade development and food security. The study aims to analyze the production costs and rice import and export volumes between Southwest China and the main rice-producing countries in Southeast Asia. For the current study, rice sown area, yield, production, and import/export data were collected for 1978-2021 based on the FAO statistical database. Comparative analyses of the planted area, unit area production, total production, import and export, market share, trade potential, and trade competency of rice in China’s southwestern region and the major rice-producing countries in Southeast Asia were performed. The study revealed that rice cultivated area and total production in the major rice-producing countries of Southeast Asia generally increased from 1978 to 2021, with Indonesia, Vietnam, and Thailand being among the top three major rice-producing countries in Southeast Asia since 1978. Cambodia’s area under rice cultivation has increased significantly, with its total rice production reaching from 1 million tonnes in 1978 to 11.41 million tonnes in 2021. The import of rice in the southwestern region of China is increasing, and the volume of rice trade in 1978 was nearly 12 times higher than that in 2021. In addition, Thailand and Vietnam are the major rice exporting countries, accounting for 53.49% and 35.10% of the rice export volume, and they can be used as potential countries for future rice trade with the southwestern region of China. In conclusion, increasing agricultural inputs to ensure regional food security, deepening rice industry chain reform, expanding the rice trade market in Southeast Asia, and establishing a high-standard free trade zone to smooth regional trade in rice can strengthen trade exchanges and foster new trade growth.